Cutaneous Reactions Following COVID-19 Vaccination: A Review of the Current Literature - Martora F; Battista T; Marasca C; Genco L; Fabbrocini G; Potestio L (Dove Medical Press, 2022)
Fabrizio Martora, Teresa Battista, Claudio Marasca, Lucia Genco, Gabriella Fabbrocini, Luca Potestio Section of Dermatology, Department of Clinical Medicine and Surgery, University of Naples Federico II, Naples, ItalyCorrespondence: Fabrizio Martora, Section of Dermatology, Department of Clinical Medicine and Surgery, University of Naples Federico II, Naples, Italy, Tel +39 - 081- 7462457, Fax +39 - 081 - 7462442, Email fabriziomartora92@libero.itAbstract: The outbreak of coronavirus disease 2019 (COVID-19) represented a new worldwide challenge, strongly impacting on the global economy, overall health and lifestyle. Since then, several strategies have been adopted to contain the widespread of infection. Among these, vaccination is currently the most important measure to fight against the pandemic. However, several concerns such as slower-than-hoped-for rollout, the hurried approval with limited data, the mechanism of action (in particular mRNA-based), and the uncertain duration of protection they afforded were initially raised. Moreover, even if cutaneous reactions have been rarely reported in clinical trials, global mass vaccination showed several dermatologic reactions not initially recognized, leaving dermatologists to decide how to diagnose and treat them. In this scenario, dermatologists should be ready to promptly recognize these clinical manifestations. Thus, the aim of this manuscript is to review current literature on cutaneous reactions following COVID-19 vaccination, particularly inflammatory dermatological diseases, in order to help clinicians to better understand these dermatological conditions and to provide an extensive overview of all the vaccine-related skin manifestations.Keywords: cutaneous reactions, COVID-19 vaccinations, side effects